Mengungkap Sistem Pengelolaan Keuangan Pada Subak Multikultur - Gede Pradnyanta Wibawa; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2022)
The purpose of this research reveals how the Financial Management System Subak Multicultural in Subak Pancoran, Panji Anom Village. This research was conducted using a qualitative approach that encourages understanding of the substance of an unknown phenomenon, with data collection techniques, namely observation, interviews, literature study and document analysis. Furthermore, this data was processed by 3 (three) data analysis techniques: data reduction, data presentation, and conclusion drawing. The results showed that Subak Pancoran was guided by the correct systematics in financial management, starting from planning, use, recording, to accountability. All of these indicators as a whole have been met with HR (human resources) managers who are very honest and responsible. However, there are obstacles in its management, namely ambiguity and grants that prohibit use for one sector of subak krama activities. Therefore, all parties struggle to find solutions so that there will be no element of social inequality that will cause division or weaken integration values in Subak Pancoran.